RESEARCH OF INSTANT POWDER DRINK DAYAK ONION (Eleutherine Palmifolia, (L.) Merr) AND PINEAPPLE (Ananas Comocus (L.) Merr) - Diana Silvy; Ismed Ismed; Mentari Cyntia Rifni (University of Sultan Ageng Tirtayasa, 2020)
Instant powder drink is food processed in the form of powder, easily dissolved in the water, practical in serving and has a long shelf life because of it’s low water content. In this study instan powder drink were made using the raw material from the mixing of dayak onion juice with pineapple juice. This research used a completely randomized design (RCD) with 5 treatments and 3 replication. Data were analyzed statistically using ANOVA and continued with Duncan’s New Multiple Range Test (DNMRT) at the 5% level. The treatment in this study was the mixing of dayak union juice and pineapple juice in the formulation A (90:10), B (80:20), C (70:30), D (60:40), E (50:50). From the results of receiving the instant powder drink of dayak union and pineapple juice ranges from usual preference to like. The most preferred treatment is treatment E with colour value of 3,25 (ordinary), aroma of 3,65 (like) and taste of 3,70 (like). The study aims to determine the best composition of instan powder drink in terms of organoleptic and chemical, physical and microbiological characteristic.